Case report: Diagnosis of ADCY5-related dyskinesia explaining the entire phenotype in a patient with atypical citrullinemia type I - Pontrucher, Audrey; Barth, Magalie; Ziegler, Alban; Chao de la Barca, Juan Manuel; Mirebeau-Prunier, Delphine; Reynier, Pascal; Homedan, Chadi (Frontiers in Neurology, 2023)
In this case study, we report the case of a 13-year-old girl with citrullinemia type 1 (MIM #215700), an autosomal recessive inherited disorder of the urea cycle, which was confirmed by the identification of a homozygous pathogenic variant in the argininosuccinate synthetase 1 (ASS1) gene. However, the patient presented abnormal hyperkinetic movements with global developmental delay and clinical signs that were not fully consistent with those of citrullinemia type 1 or with those of her siblings with isolated citrullinemia type 1. Exome sequencing showed the presence of a de novo heterozygous pathogenic variant in the adenylate cyclase type 5 (ADCY5) gene. The variant confirmed the overlap with the so-called ADCY5-related dyskinesia with orofacial involvement, which is autosomal dominant (MIM #606703), a disorder disrupting the enzymatic conversion of adenosine triphosphate (ATP) to cyclic adenosine monophosphate (cAMP). In addition to the citrullinemia-related low-protein diet and arginine supplementation, the identification of this second disease led to the introduction of a treatment with caffeine, which considerably improved the dyskinesia neurological picture. In conclusion, this case highlights the importance of clinical-biological confrontation for the interpretation of genetic variants, as one hereditary metabolic disease may hide another with therapeutic consequences. Summary This article reports the misleading superposition of two inherited metabolic diseases, showing the importance of clinical-biological confrontation in the interpretation of genetic variants.